Developing Religious Values through the Diniyah Takmiliyah Wustha Program in Shaping Students’ Noble Character - Tati Kurniawati; Marwan Setiawan (CV. Media Digital Publikasi Indonesia, 2025)
This study examines the implementation of Madrasah Diniyah Takmiliyah Wustha (MDTW) as a strategic effort to develop students’ religious character in two public junior high schools: SMPN 1 and SMPN 3 Rajadesa, Ciamis Regency. Using a qualitative case study approach, data were collected through participatory observation, in-depth interviews with school principals, MDTW teachers, students, and parents, as well as curriculum documentation analysis. Thematic analysis was applied to identify patterns of transformation and institutional impact. The findings reveal that MDTW is implemented through a three-layer integration model structural, cultural, and social which effectively supports character development. Students experience a three-phase transformation: cognitive awakening, behavioral internalization, and spiritual actualization. The program led to a 72% decrease in disciplinary violations, a 58% increase in spiritual engagement, and a 65% improvement in conflict resolution skills. Comparative analysis also shows that moral and behavioral outcomes in MDTW schools are significantly better than in schools without similar programs. Despite its success, the implementation of MDTW faces several challenges, including limited funding allocation, uneven management commitment, and student resistance. The study introduces a Spiritual Ecosystem Framework that highlights the importance of curriculum design, environmental support, and stakeholder engagement in sustaining religious education. The study concludes that MDTW is a viable model for moral education in the digital age and recommends national quality standards, teacher training in digital Islamic pedagogy, and holistic spiritual assessment systems.